A Case of Unusual Coexistence of Keratoconus and Optic Disc Pit. (March 2015) - Aslankurt, Murat; Aslan, Lokman; Aksoy, Adnan; Başkan, Ahmet M.
Abstract Purpose: To report a case of unusual coexistence of keratoconus and optic disc pit. Methods: A 29-year-old male patient followed up because of the left established and right subclinical keratoconus presented with blurred vision on the left eye that occurred within days. In addition to a comprehensive ophthalmic examination, computerized corneal topography (CT), corneal pachymetry, and optical coherence tomography (OCT) examination were performed. Results: The corneal CT showed a mild keratoconus pattern, with a minimum corneal pachymetry of 472 in the right eye and moderate keratoconus pattern with a minimum pachymetry of 435 micron in the left eye. The OCT scans showed the presence of the optic disc pit and related maculopathy. Conclusions: This is the second report of the coexistence of keratoconus and optic disc pit in the literature. The association of these two entities is therefore less likely to be accidental. Further histopathological studies will be necessary to explain this relationship between two entities.